Diversity of Aquatic Beetles (Dytiscidae) along the Altitudinal Gradient and its Relationship with Physico-Chemical Parameters of Water at Tashiding, Tsendagang and Gozhi Gewogs, Dagana, Bhutan - Blon, Wangchuk; Dendup, Tashi; Dorji, Cheten; Wangdi (International Journal of Environment, 2023)
Dytiscidae plays a vital role in the ecosystem; purifies water and serv es as the prey on many organisms. This family of aquatic beetles as predators feeds on small organisms. They are sensitive to environmental changes, it is used as a biodiversity indicator and also a tool for conservation assessment. This study assessed the diversity of Dytiscidae in relation to physico-chemical parameters of water using stratified random sampling at three Geogs in Dagana. Furthermore, the relationship of Dytiscid diversity and taxon richness with the physico-chemical parameters of the lentic and the lotic water bodies along the altitudinal gradient were determined and collected specimens. The total 664 individuals were collected in which five subfamilies of Dytiscidae, 12 genera and 17 species were identified. Pearson’s correlation showed moderately negative correlation between the species diversity and taxon richness based on altitude and pH (p < 0.05). Temperature had moderate positive correlation with species diversity of Dytiscidae. Canonical correspondence analysis (CCA) showed temperature had an effective determining factor for distribution of Dytiscidae. Kruskal Wallis test among different habitats and altitudinal strata showed significant difference in Dytiscids diversity and taxon richness (p < 0.05). The diversity and richness showed a decreasing trend when the altitude increased. The highest diversity was found in marshy area (H = 2.36) and second altitude stratum (800 – 1200 masl) (H = 2.07) in the current study area. Therefore, the best conservation strategy of Dytiscidae could be to protect these areas before they are degraded.